Chinese and Malay Interaction in West Kalimantan: Discovering Harmony in Diversity of Ethnic Groups through Local Wisdom - Atmaja, Dwi Surya; Kurnanto, M. Edi (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2018)
This research aims to explore the wisdom of socio-religious interaction and tradition in West Kalimantan Malay society towards Chinese ethnic. This research recommends local wisdom as a media to downgrade the tension of social political and religious interactions that have been perceived recently as the threat of national and even global harmony. The source of data in this study was Deutro Malay ethnic and Chinese ethnic at Teluk Pak Kedai. The data was determined through purposive techniques by considering the two circles of key informants, i.e. information from the closest circumference (epicentrum) with the source of wisdom, which in this study consists of a closed circle from the figure of Haji Ismail Mundu and Foundation (China), and information from peripherals. The Data collected through in-depth interviews, observations and documentation were then analyzed by using qualitative normative cycle formats to be presented in thematic classifications in line with the focus and research questions. This study concluded that the theological characteristics of Haji Ismail Mundu can easily adjust to the characteristics of the Chinese. The harmonious reciprocity between the two traditions, in terms of the inter-ethnic reciprocal relationship manifested in the Teluk Pak Kedai, is unique as seen in the respect and appreciation given by the Confucian Chinese in the form of displaying a photo of Haji Ismail Mundu in the Phe Kong worshiping in homes. Every potential of conflict has always been successfully overcome by “intensity” and “modesty” through the figure of Haji Ismail Mundu and being committed to preserve his heritage.